ʺThe economic franchise for African Americans: Reverend Leon Howard Sullivan’s contributionˮ, - KPOHOUE, FERDINAND (My University, 2015)
African Americans were not accepted to work together with Whites even after the ratification of the 13th Amendment on January 31, 1865. Reverend Leon H. Sullivan (1922 – 2001) identified some strategies to oblige the Whites to accept Blacks to work together with them. He innovated the selective patronage to boycott companies that rejected Blacks. As a result, Blacks were accepted but they lacked skills and experience to be as efficient as Whites. Sullivan created the OIC, a training center, in order to empower Blacks as well as other minority groups to become competitive. The outcome was amazing, OIC centers spread everywhere in America. Millions of Blacks were trained and were hired. So black people identified as hellions, drunkards, or bums in society could become misters after a stay in OIC training centers. The objective of this research paper is to assess the impacts of the OIC on the Blacks in America in terms of their social regard and moral satisfaction. Sullivan’s experience is a step forward in the process of integration and betterment of the conditions of African Americans in the 20th century.
Keywords: African- Americans; OIC; selective patronage; economic; franchise; black-owned businesses